The effectiveness of berberine on noise-induced hearing loss: a rat model - Kilic,Korhan (2022)
SUMMARY OBJECTIVE: Noise-induced hearing loss is a preventable form of hearing loss that has serious social and economic impacts. This study aimed to investigate the protective effect of berberine, a potent antioxidant and anti-inflammatory agent, against Noise-induced hearing loss. METHODS: After applying distortion product otoacoustic emission, 28 female Sprague-Dawley rats were randomly divided into four groups. Group 1 was designated as acoustic trauma group, and rats in this group were exposed to white noise for 12 h at an intensity of 4 kHz 110 dB sound pressure level. Group 2 was the control group. Group 3 was designated as the berberine group, and 100 mg/kg of berberine was administered to rats in this group by intragastric lavage for five consecutive days. Group 4 was designated as the acoustic trauma+berberine group. distortion product otoacoustic emission was repeated on the 6th day of the study and cochlear tissues of rats were dissected for histopathological and immunohistochemical analyses after sacrificing rats. RESULTS: The distortion product otoacoustic emission results showed a significant decrease in signal-noise ratio values at higher frequencies in rats of the trauma group compared to those in other groups. Acoustic trauma caused severe histopathological impairment at cochlear structures together with severe 8-hydroxy-2-deoxyguanosine expression. Rats in the acoustic trauma+berberine group showed mild histopathological changes with mild 8-hydroxy-2-deoxyguanosine expression and better signal-noise ratio values. CONCLUSION: The histopathological and audiological findings of this experimental study showed that berberine provides protection in Noise-induced hearing loss and may have the potential for use in acoustic trauma-related hearing losses.